Innovation and Entrepreneurship in the Circular Economy: A Systematic Review - Safitri, Camelia (Penelitian dan Pengembangan Ilmu, 2024)
The circular economy is an important strategic approach in promoting global sustainability by separating economic growth from environmental degradation. The transition to a circular economy leverages digital technology to increase resource efficiency, reduce waste and encourage collaboration among stakeholders. This research aims to explore the role of digital technology in supporting entrepreneurial innovation in the context of a circular economy. This research uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method to collect and analyze relevant literature from reputable databases such as Scopus, Web of Science, and ScienceDirect. The research results show that digital technologies, such as the Internet of Things (IoT), artificial intelligence (AI), and big data analysis, have a significant role in facilitating entrepreneurial innovation and accelerating the transition to a circular economy. The implications of this research are important for policy makers and business practitioners in designing more sustainable and efficient strategies. This research also makes an academic contribution by filling the gap in the literature regarding the interaction between digital technology and entrepreneurial innovation in the circular economy, as well as providing practical recommendations for implementation in various industrial sectors.